A faster serve has more impact on success for female elite tennis players than males. (4th July 2021) - Brown, E. G.
ABSTRACT: The impact of serve speed on serve success in tennis singles was investigated using data from The Championships, Wimbledon from 2004 to 2019. Serve speed is an important characteristic because it provides the server with a potential advantage and can therefore influence the outcome of the game. Understanding the effect of serve speed on serve success could prove useful in informing players and coaches about the most advantageous serve strategy. Significant positive correlations were found between serve speed and the percentage of points won by both male and female players, on their first and second serves. However, this relationship was more pronounced in the first serve than the second serve for both sexes, and in the female game more so than in the male game. This implies that other service characteristics, such as spin and placement, could be more influential in the male game. No significant relationships were found between serve speed and percentage of points that were aces. Furthermore, the results of this study support the use of the common faster first serve with slower second serve service strategy at The Champions, Wimbledon.